Trends in Research on Traditional Chinese Health Exercises for Improving Cognitive Function: A Bibliometric Analysis of the Literature From 2001 to 2020 - Li, Wenlong; Weng, Linman; Xiang, Qiuping; Fan, Tonggang (Frontiers in Public Health, 2022)
Although previous studies have investigated the ability of traditional Chinese health exercises (TCHEs) to improve cognitive function, few have utilized bibliometric analyses to address this topic. We aimed to investigate the current status of and developmental trends in this field from 2001 to 2020. We searched the Web of Science Core Collection (WoSCC) for all research publications on cognitive function in relation to TCHEs. CiteSpace V was used to analyze the number of papers, countries, institutions, journals, authors, and citations. We identified hotspots and trends in the field by drawing co-citation reference and co-occurrence keyword maps. From 2001 to 2020, 406 relevant articles were published in the WoSCC, with a gradual increase in the annual number of publications. The three countries/regions with the most publications were the Chinese mainland, the United States, and Canada. Six universities from China and four from the United States were identified as the top 10 institutions. Most research was conducted at universities. Evidence-based Complementary and Alternative Medicine was identified as the most productive journal. Together, these findings indicate that TCHEs have received increasing attention as a method for improving cognition.